Pengaruh Harga, Promosi, Dan Brand Image Terhadap Keputusan Pembelian Skincare Scarlett Pada Mahasiswa Universitas Semarang - Naini Rizka Amalia; Susanto Susanto; Citra Andriani; Iza Safitri Dewi; Arif Afriady (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The purpose of this study was to determine the effect of price, promotion and brand image on consumer purchasing decisions at Semarang University students. The research method used is quantitative method with multiple linear regression analysis techniques. Questionnaires were distributed to the respondents totaling 100 respondents. The results of this study, namely price, promotion and brand image have a positive and significant effect on purchasing decisions. Price has a positive and significant effect on purchasing decisions. Promotion has a positive and significant effect on purchasing decisions. Brand image has a significant positive effect on purchasing decisions